Analysis of Injection Sclerotherapy and Hemorrhoidectomy - Shahida Baloch, Habib Ur Rehman Khan Toor, Shahnwaz Leghari, Lal Shah, Mamona, Kashif Ali Shah (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To conduct a comparative analysis between hemorrhoidectomy and injection sclerotherapy in the treatment of hemorrhoids. Study design: Comparative study Place and duration: Peoples University of Medical & Health Sciences for Women (PUMHS-W) Nawabshah Pakistan from January 2019 to January 2020. Methodology: This study included 100 patients selected randomly who had grade II and grade and for grade III hemorrhoids hemorrhoidectomy cases were selected randomly but for injection sclerotherapy only those cases were included who were not willing for hemorrhoidectomy. . Out of which 50 belonged to the hemorrhoidectomy group and 50 belonged to the injection sclerotherapy(IST) group. All the parameters of these patients were analyzed and recorded, and statistical analysis was performed on SPSS version 22. Results: We have observed that among IST (Group 1), 32 patients (64%) exhibited excellent improvement, 10 patients (20%) exhibited moderate improvement, and 8 patients (16%) exhibited no signs of improvement. Similarly, 70% of patients of hemorrhoidectomy (Group 2) exhibited excellent improvement, 20% of patients exhibited moderate improvement, and 10% of patients exhibited no signs of improvement. Similarly, 20% of patients in group 1, and 100% of patients in group 2 required analysis till 48 hours of the procedure. Conclusion: Injection sclerotherapy is effective and should be considered to treat grade II hemorrhoids whereas hemorrhoidectomy should be considered only when treating grade III hemorrhoids.